SOSIALISASI PENGENALAN PENCAK SILAT KUNTU MELALUI VIDEO DOKUMENTER SEBAGAI UPAYA PELESTARIAN BUDAYA LOKAL MANCILAN, KELURAHAN POHJENTREK, KOTA PASURUAN - SUBAGIO, DYAJENG PUTERI WORO (Fokus ABDIMAS, 2024)
Pencak silat Kuntu is a traditional martial art from Mancilan, Kelurahan Pohjentrek, Kota Pasuruan, rich in cultural values and philosophy. However, with the rapid advancement of modernization and popular culture, the popularity of Pencak Silat Kuntu has declined, particularly among the younger generation. This community service activity aims to introduce Pencak Silat Kuntu as part of efforts to preserve local culture in Kelurahan Pohjentrek. The target participants were 50 fifth-grade students from SD Pohjentrek I. The method employed was a socialization session through the screening of a documentary video that presents the history, philosophy, and fundamental movements of Pencak Silat Kuntu. This initiative successfully enhanced students' understanding of the importance of local cultural preservation, with 90% of participants demonstrating improved knowledge. Furthermore, 70% of students expressed interest in furthering their study of pencak silat. This activity aims to foster awareness of the significance of safeguarding local cultural heritage and encourages youth engagement in the preservation of traditions. The involvement of schools as formal educational institutions is expected to serve as a bridge between local traditions and the younger generation for the sustainability of this culture in the future.